Night eating, weight, and health behaviors in adults participating in the Daily24 study. (April 2022) - Lent, Michelle R.; Atwood, Molly; Bennett, Wendy L.; Woolf, Thomas B.; Martin, Lindsay; Zhao, Di; Goheer, Attia A.; Song, Shanshan; McTigue, Kathleen M.; Lehmann, Harold P.; Holzhauer, Katherine; Coughlin, Janelle W.
Abstract: Background: Night eating syndrome (NES) is associated with adverse health outcomes. This study evaluated the relationship between night eating severity, weight, and health behaviors. Methods: Participants (N = 1017; 77.6% female, mean Body Mass Index (BMI) = 30.5, SD = 7.8 kg/m 2, age = 51.1, SD = 15.0 years) were recruited from three health systems. Participants completed the Night Eating Questionnaire (NEQ) and questionnaires assessing sleep, chronotype, physical activity, diet, weight, and napping. Results: In the overall sample, higher NEQ scores were associated with higher BMI ( p < .001) and consumption of sugar-sweetened beverages ( p < .001), as well as lower fruit/vegetable consumption ( p = .001). Higher NEQ scores were associated with increased odds of having overweight/obesity ( p < .001), eating fast food ( p < .001), moderate-vigorous physical activity ( p = .005), and smoking ( p = .004). Participants who exceeded the screening threshold for NES (n = 48, 4.7%) reported elevated BMI ( p = .014), an increased likelihood of overweight/obesity ( p = .004), greater sugar-sweetened beverages consumption ( p < .001), napping less than twice per week ( p = .029), shorter sleep duration ( p = .012), and a later chronotype ( M = 4:55, SD = 2:45). Conclusion: Night eating severity was associated with obesity and intake of fast food and sugar-sweetened beverages. Interventions to address night eating and associated behaviors may enhance the efficacy of weight management interventions and promote engagement in positive health behaviors. Highlights: Night eating severity was associated with an increased risk of obesity. As night eating severity increased, fruit/vegetable consumption decreased. Sugar-sweetened beverages and fast food intake were associated with night eating. Night eating was associated with shorter sleep duration and a later chronotype.